Administrasi Sarana dan Prasarana Pendidikan - Saskia Azhara Putri; Sakban Sakban; Dwi Yana Alidia Fitri; Reni Ramita Sari; Firly Fadila Julita; Alvi Mahessa (Student Research Journal, 2024)
In this article the author will explain the administration of facilities and infrastructure in the school environment. Facilities and infrastructure administration is one of the most important things in education. All activities in schools will require facilities and infrastructure, both directly and indirectly so that they will support the course of the learning process of education. Administration of facilities and infrastructure is very supportive of achieving educational goals. The positive and negative educational environment depends on maintaining the school facilities and infrastructure. Maintenance and management of infrastructure must be managed properly, but there are still some that have not been implemented optimally. Therefore, the author intends to make this article so that it can be used as a reference in managing educational facilities and infrastructure.